Pons et cella penaria – Die Bedeutung Siziliens für die Entwicklung des Imperium Romanum ausgehend von Ciceros „Verrinen“ - Ferdinand Kleyhons (Historia.scribere)
Pons et cella penaria – The importance of Sicily for the formation of the Roman Empire on the basis of Ciceros “In Verrem”